Perancangan Sistem Informasi untuk Meningkatkan Pemasaran Paket Wisata CV Animedia Tour Berbasis Mobile - Sumantri, Raden Bagus Bambang; Walidy Rahman Hakim; Asharryadi Noegroho; Safitri Dwi Lestari; Syifa Marsyanda Chairunnisa (Universitas Harapan Bangsa, 2025)
The tourism sector plays a vital role in boosting Indonesia's economy, with numerous attractive destinations. Along with the rapid development of information technology, this sector faces a significant opportunity for transformation through the implementation of mobile-based digital systems. CV Animedia Tour, a company providing travel services, faces challenges with limited promotional reach and a manual reservation system that hinders operational efficiency. This research aims to design a mobile-based information system that can enhance marketing efficiency and user convenience. This system allows customers to easily access information, make bookings, and receive updates on the latest travel offers. The methodology used in this research is prototyping, which involves several stages such as interviews, observations, and literature reviews. The results of the evaluation using the System Usability Scale (SUS) show that the application is well-received by users, with an average score of 72.5, indicating a high level of usability. The implementation of this system not only improves operational efficiency but also expands market reach and increases customer satisfaction. Moving forward, the company should continue to develop the application based on user feedback to ensure its relevance and effectiveness.